Vessel co‐option in primary human tumors and metastases: an obstacle to effective anti‐angiogenic treatment?. (8th July 2013) - Donnem, Tom; Hu, Jiangting; Ferguson, Mary; Adighibe, Omanma; Snell, Cameron; Harris, Adrian L.; Gatter, Kevin C.; Pezzella, Francesco
Abstract Angiogenesis has been regarded as essential for tumor growth and progression. Studies of many human tumors, however, suggest that their microcirculation may be provided by nonsprouting vessels and that a variety of tumors can grow and metastasize without angiogenesis. Vessel co‐option, where tumor cells migrate along the preexisting vessels of the host organ, is regarded as an alternative tumor blood supply. Vessel co‐option may occur in many malignancies, but so far mostly reported in highly vascularized tissues such as brain, lung, and liver. In primary and metastatic lung cancer and liver metastasis from different primary origins, as much as 10–30% of the tumors are reported to use this alternative blood supply. In addition, vessel co‐option is introduced as a potential explanation of antiangiogenic drug resistance, although the impact of vessel co‐option in this clinical setting is still to be further explored. In this review we discuss tumor vessel co‐option with specific examples of vessel co‐option in primary and secondary tumors and a consideration of the clinical implications of this alternative tumor blood supply.